Entre “luzes” e “trevas”: o padroado e as origens da reforma pombalina da Universidade de Coimbra - Carvalho, Flávio Rey de (2019)
This research reports on the remote origins of the Pombaline Reform of the University of Coimbra, guided by the dynamics of power relations between State and Church, under the modus operandi of the “right of patronage”. Marked by the intertwining between the political and religious spheres, such circumstance, increased the influence of the Portuguese kings on their territories, creating conditions conducive to the development of regalist ambitions, whose zenith occurred in the 1760s. The categories of “order” and “recapitulated traditions” are used as a theoretical presupposition to envision the “Lights” in Portugal, often overshadowed by a certain conception of “Enlightenment” - prone to the radical devaluation of religious phenomena and aligned with a model of “modernity” unilaterally based on the principle that, under the influence of modern rationalization, religion would be doomed to decline. Based on “official” sources (such as “decrees”, “laws”, “statutes” and some “works” whose contents are related to the “attempts” of change), that is, through reflection based on formal records, the study supports the hypothesis that the measures taken by the Crown during the third quarter of the eighteenth century, which would include the expulsion of the Jesuits in 1759, were not taken to combat religion or Catholicism, but to give power for the establishment of an “order” that was convenient to the interests of the “common good” of the Portuguese monarchy. Thus, some of the embryonic elements of the “Pombaline Reforms”, which would culminate in a review of higher education between 1771 and 1772, happened as a consequence of the process of resurgence of the regal power through the patronage regime in the years 1400 and 1500